How to reduce the exposure risk of medical staff from SARS-CoV-2 by reducing environmental contamination: Experience from designated hospitals in China - Zeng, Cui; Liu, Hengzhuo; Jiang, Yuling; Fu, Yuanyu; Liu, Yuan; Chang, Wei; Li, Tingting; Huang, Xun; Li, Chunhui (Frontiers in Public Health, 2022)
Background: We found an increased environmental contamination since August 18, 2021 in a designated hospital only for COVID-19 patients in China, which may lead to an increased risk of high exposure for medical staff. Methods: From August 18 to 21(before intervention) and August 22 to 28(after intervention), 2021, 6 infection isolation rooms with windows for ventilation and other auxiliary areas had environmental samples taken at 105 and 129 sites before routine cleaning for the day, respectively, and PPE samples from 98 medical staff at 482 sites exiting the patient rooms/contaminated areas also were collected. From August 22 to August 24, 2021, we have taken some measures to reduce the positivity of environmental contamination based on sampling and inspection results. Findings: We found the positivity for environmental surfaces and PPE samples of critical patient(37.21%&27.86%) was much higher than severe patients(25.00%&12.50%) and moderate patients(0.00%&0.00%). Through investigation, we found that the critically ill patient had emergency tracheal intubation and rescue on August 18 due to condition changes. And the ventilator tube used in the first aid did not match the ventilator, the ventilator tube fell off multiple times within August 18 to August 21. We believe this may be the reason for the increased contamination of environmental surfaces and PPEs from critically ill patient's room, and also indirectly contaminated the potentially contaminated areas. The contamination positivity of the environmental surfaces and PPEs were reduced by replacing the appropriate ventilator catheter, limiting the number of people entering the isolation room at the same time, increasing the frequency of environmental disinfection, standardizing the undressing process, setting up undressing monitoring posts to supervise the undressing process, and no spreading of virus infection in hospital occurred at the end of the epidemic. Conclusion: This study led to the conclusions that SARS-CoV-2 was distributed on object surfaces in isolation rooms mainly by touchment, and the environmental surfaces and PPEs contamination was greater in the room of patients with higher severity for more medical operation and higher surface touchment.